Analisis dan Perancangan Sistem Informasi Promosi Berbasis Web Pada Asosiasi UMKM Muaro Jambi - M. Yusuf, M. Yusuf; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2018)
Technology that supported by information system need in globalization era have been felt of sociaty and importantthing one of them is internet, business competition demanding a business man keep up with market developments andwillingness. UMKM Association of Muaro Jambi have limited time contraints in it is product promotion, with theresult that the management marketing done by UMKM Association is still not good. Hence, the main problem facedout is marketing especially promotion. There is no promotion media online base in UMKM Association of MuaroJambi.Analysis and system planning method with UML object oriented approach. In this research will be produce aprototype of information system of promotion can be implemented, with the result that produce information system ofpromotion will apply by UMKM Association of Muaro Jambi.